Employee Retention Factors in Nepali Insurance companies - Ghimire, Pitambar (Journal of Business and Social Sciences, 2018)
Employee retention is complex phenomenon that requires strategic orientation towards retention factors. The objective of the study is to find out factors influencing employee retention and examine them with retention intention. The 125 respondent (sample) with different categories are taken from various insurance companies. The stratified sampling method is used to make the sample representation and convenient sampling has been used to select the sample unit. Descriptive statistics, correlation analysis, hypothesis testing are carried out to examine the retention intention. The research paper concludes that the employee retention is complex management job and it needs high level commitment. All retention factors have positive impact on retention intention.